Eksperimental Bentuk Sudu Turbin Pelton Setengah Silinder Pada Variasi Sudut Keluaran Air Untuk Pembangkit Listrik Tenaga Picohydro - Sutomo, Sutomo; Arief Budiman, Arief Budiman (JURNAL AGRI-TEK, 2014)
Water turbine is prime mover that converts the kinetic energy of the water flow at high velocity into mechanical energy in the form of turbine wheel rotation. One type is a water turbine is pelton turbine, where the main components is runner where was mounted around a hemispherical -shaped blade and nozzle . During this form of pelton turbine blades are widely used form of bowls (bucket), with the size and number of a particular blade, while the other form is rarely used . To determine how much influence the change in shape of the blade to the turbine generated power, it is necessary to research on changes in the shape of the pelton turbine blade performance. In this study aims to do exactly the pelton turbine performance experiments on the effect of changes in the characteristics of the type of half - cylinder blades . Stages of the research is to design and plan a pelton turbine with several variations of the output angle of water on a half - cylinder - shaped blade, and then investigate the optimization of the output angle of water on the turbine blade pelton turbine performance . The parameters measured in the test is the water flow rate, water pressure at the nozzle , turbine shaft rotation and torque . Specified parameters and is variable in this study is the output angle of water on the blade, namely : 1700, 1730, 1760 and 1790. Results obtained from this research is pelton water turbine with output angle of water on the blade (β2) of 1790 produces mechanical power and highest efficiency of 462.60 watts, with 71.62 % mechanical efficiency and overall system efficiency of 30.02 % . Differences lowest turbine mechanical power (at β2 = 1700) and the highest (at β2 = 1790) amounted to 9.12 watts, or 1.97 %Keywords : Pelton turbine, nozzle, vanes, Angle Output Water